Enhancement of copper toxicity in cultures of Dictyosphaerium pulchellum (Chlorophyceae) by mucilage removal - de la Peña, Laura G. (2005)
Extracellular mucilage from cells of Dictyosphaerium pulchellum Wood 1872 was removed by controlled ultrasonication. Batches of exponentially growing cells, with and without mucilaginous capsules, were incubated during 48 hours with 50, 100, 200 and 300ug.l-1 of copper (added as copper sulfate). Free divalent cation concentration at the beggining of the experiment was estimated by MINEQL+. Both cellular yield and total chlorophyll content were negatively affected by the increment of copper concentration in the incubation media. Mucilage removal enhanced susceptibility to bleaching, while it did not modify significantly cellular density at the end of the experiment.